DEEP INTERACTIVE LEARNING ACTIVITIES FOR IMPROVING YOUNG LEARNERS’ ENGLISH VOCABULARY AT PPA IO- 0133 KRAMMER HILINA’A - Afore Tahir Harefa; Wina Anjelina Harefa; Sharley Grace Mendrofa; Christian Pradana Putra Zalukhu; Friska Putri Waruwu; Oktoberlianus Zendrato (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community service program was conducted to address young learners’ limited basic English vocabulary in a non-formal educational setting at PPA Krammer Hilina’a Church. The program aimed to improve students’ vocabulary mastery through deep learning–based interactive learning activities that emphasize meaningful understanding and active use of language. The participants were 23 students aged 9 to 11 years. The program was implemented in two cycles using planning, action, observation, and reflection stages. Interactive activities such as gesture-based learning, picture-based tasks, pair work, and guided sentence construction were employed to support deep learning through repeated exposure and contextual practice. Quantitative data were collected through vocabulary tests, while qualitative data were obtained from observation sheets and field notes. The results indicated a significant improvement, as students in the Good and Very Good categories increased from 21.74% in Cycle 1 to 69.57% in Cycle 2, while students in the Poor and Very Poor categories decreased from 39.13% to 0%. These findings demonstrate that deep learning–based interactive learning activities effectively support basic English learning in community-based programs.